ENT300 Fundamentals of Entrpreneurship : Business Plan Happy Day Kids Nursery / Mohamad Nazrin Musaini... [et al.] - Musaini, Mohamad Nazrin; Yusuf, Hadri; Sanggai, Cyrus; Usung, Janet; Cloude, Jean (2014)
We have made decision to form a pannership company with 5 shareholders. Each of the shareholders been given specific job based on their experiences, knowledge and skill such as General Manager, Administrative Managers Marketing Manager, Operational Manager, and Financial Manager. Each of our members is very professional In their own areas. As a company that based on service, each department have its own role and responsibilities in order to expand our busmess and achieve company's goal. As a head of the company, General Manager must possess the ability to control the company and set up vision and mission of the company. Administration manager main function is activities of planning, organizmg, leading and controlling. Marketing manager is important to encourage and increase sales revenue. As for Operational manager, it is their duty to monitor company activities to ensure the business meet the customers' expectations. Financial plan is the most crucial aspect to improve company financial performance which was handled by the Financial manager.